2019
DOI: 10.33854/heme.v1i1.215
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko yang Berhubungan dengan Kejadian Pneumonia pada Balita di Puskesmas Ikur Koto Kota Padang

Abstract: The occurrence of pneumonia is related to many factor such as the age of toddler, sex of the toddler, the low birth weight, history of giving exclusive breastfeeding, measles immunization history, DPT immunization history, Hib immunization history, mother’s occupation, mother’s education and family members who are smoker. The aim of this research was to find out risk factor related to pneumonia occurrence in toddler in Puskesmas Ikur Koto Padang city in 2017. This research used case control design, sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 2 publications
4
8
1
11
Order By: Relevance
“…In that study showed the OR score obtained was 3.1, which meant that mothers with a low level of education have a 3.14 times greater risk of their child (<2 years) developing pneumonia compared to mothers who have a high level of education. This was in line with research by Rigustia, Zeffira, & Vani (2019) that also stated that mothers with low education have a 0.95 times greater risk of having children with pneumonia than mothers who have higher education. A mother's education will affect the quality of care given to their child (Mustikarani, Rahardjo, Qadridjati, & Prasetya, 2019).…”
Section: Correlation Of Mothers' Characteristics With the Incidence Osupporting
confidence: 90%
See 2 more Smart Citations
“…In that study showed the OR score obtained was 3.1, which meant that mothers with a low level of education have a 3.14 times greater risk of their child (<2 years) developing pneumonia compared to mothers who have a high level of education. This was in line with research by Rigustia, Zeffira, & Vani (2019) that also stated that mothers with low education have a 0.95 times greater risk of having children with pneumonia than mothers who have higher education. A mother's education will affect the quality of care given to their child (Mustikarani, Rahardjo, Qadridjati, & Prasetya, 2019).…”
Section: Correlation Of Mothers' Characteristics With the Incidence Osupporting
confidence: 90%
“…The OR score obtained was 3.50, meaning that children aged less than two years who were not given exclusive breastfeeding had a 3.50 times greater risk of developing pneumonia compared to children who were given exclusive breastfeeding. This was in line with research conducted by Rigustia, Zeffira, & Vani (2019) stating that exclusive breastfeeding is one of the dominant factors of pneumonia with an OR score of 7.40, meaning that children who are not given exclusive breastfeeding have a 7.40 times greater risk of developing pneumonia compared to children given exclusive breastfeeding.…”
Section: Correlation Of Exclusive Breastfeeding With the Incidence Ofsupporting
confidence: 89%
See 1 more Smart Citation
“…The results obtained certainly caused some debate and were unexpected. Another research, whose results were also not in agreement, was conducted by Rigustia, Zeffira, & Vani (2019). They stated there was no relationship between nutritional status and the incidence of pneumonia in toddlers, with p value=0.79.…”
Section: Nutritional Statusmentioning
confidence: 91%
“…Pneumonia pada balita dapat menyebabkan balita yang meninggal sekitar 2.500 anak setiap harinya. Secara statistik, balita yang meninggal di seluruh dunia akibat pneumonia pada tahun 2015 adalah 16 % dari semua kematian pada balita yaitu sebanyak 920.136 anak (2).…”
Section: Pendahulununclassified